Coherent Pricing of Life Settlements Under Asymmetric Information. Issue 3 (26th July 2013) - Zhu, Nan; Bauer, Daniel
Abstract : Although life settlements are advertised to deliver a profitable investment opportunity with a low correlation to market systematic risk, recent investigations reveal a discrepancy of expected and realized returns. While thus far this discrepancy has been attributed to the (allegedly) poor quality of the underlying life expectancy estimates, we present a different explanation of the seemingly high reported expected returns based on adverse selection . In particular, we provide a coherent pricing mechanism and pricing formulas in the presence of asymmetric information with respect to the underlying life expectancies. Therefore, our study sheds light on the nature of the "unique risks" within life settlements as recently discussed in the financial press.,